El Pepitero Verdoso (Saltator similis) en la provincia de Buenos Aires, Argentina - Bodrati, Alejandro; Ferrari, Carlos; Bordón, Eduardo; Novoa, Daniel; Huergo, Rodolfo Romero (Nuestras Aves, 2001)
Este artículo no cuenta con un resumen.